KARAKTERISTIK IBU YANG MELAHIRKAN BAYI BERAT BADAN LAHIR RENDAH DI RSU SUNDARI MEDAN TAHUN 2016 - Nurjannah Nurjannah; Rasmaliah .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
2%. This research was conducted in SundariHospital Medan, it’s a descriptive research with case series design. The population of this study are 201 mothers who gave birth to infants with LBW. Samples are taken from the total population. The highest frequency distribution of LBWR for weight group is 1500- <2500 86.1%. The highest sociodemography proportion: age 20-35 years (68,7%), Moslem (88,0%),unemployed (65,7%). Based on the highest risk factor, gestational age 37-42 weeks (63,7%), parity <2 (70,6%), Interval of pregnancies with first-born child <2 years(55,2%), Hb ≥11 gr% (60,2%), no illness (97,5%) pregnancy with complication 56,2%, type of complication in early rupture of membrane (33,6%), obstetric history (59.7%). The highest proportion of infants and mothers’ discharging conditionis outpatient care which is 92,2% and 98,0% for each respectively. Based on bivariate analysis, maternal age (p = 0,605), occupation (p = 0,306), Hb (p = 0,748), maternal disease (p = 0,532), obstetric history (p = 0,476) there is no difference between proportion with classification of LBW. Gestational age’s variable (p = 0,000), parity of mother (p = 0,020), pregnancy spacing (p = 0,023), complication in pregnancy (p = 0,000) have different proportion with classification of LBW. For the hospital authority is expectedto improve records related to the birth with LBW. For the mothers, it’s suggested to check the condition of pregnancy by doing Antenatal Care for routine, maintaining the good nutrition to prevent the occurrence of LBW.The caregivers in the hospital is also expected to give more councelling for pregnant women about the important of pregnancy checking and to provide informationabout the prevention and control of LBW.